A method for preparing a collagen wound dressing
Patent Information
- Application Number
- CN202511965626.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-24
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-12-24
AI Technical Summary
然而,这类合成材料往往生物活性匮乏,其生物降解性和降解产物的生物安全性也令人担忧
本发明通过氧化黄芪多糖与羧基化水解胶原蛋白的活性功能化设计,结合羧甲基壳聚糖的桥接作用、丙烯酰胺的力学增强以及镁离子的离子交联,并通过两步法成型工艺,将天然材料的生物活性与合成聚合物的力学性能在分子和网络结构层面进行了结合,制得了具备优异力学性能的多功能水凝胶敷料。
Smart Images

Figure CN121910932B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of dressing technology, specifically relating to a method for preparing a collagen wound dressing. Background Technology
[0002] Wound dressings are medical materials used to cover wounds and create a favorable environment for healing. In addition to providing a physical barrier, preventing infection, and absorbing exudate, wound dressings also need to maintain wound moisture, promote granulation tissue growth and epithelialization, thereby accelerating the healing process. Hydrogel dressings have attracted much attention due to their unique three-dimensional network structure and high hydrophilicity. They can provide a moist healing environment for the wound, provide cooling and analgesia, and reduce secondary damage to newly formed tissue during dressing changes through their soft, moist properties.
[0003] Currently, materials used to prepare hydrogel dressings are mainly divided into two categories: natural polymers and synthetic polymers. Hydrogels based on natural polymers, such as collagen, chitosan, hyaluronic acid, and polysaccharides, are widely studied due to their excellent biocompatibility, biodegradability, and inherent bioactivity. For example, collagen is a major component of the extracellular matrix and can actively promote cell adhesion and migration; plant polysaccharides (such as astragalus polysaccharide) have been shown to have anti-inflammatory and immunomodulatory functions. However, hydrogels prepared from these natural materials generally suffer from insufficient mechanical strength, rapid swelling or degradation under the influence of body fluids, and poor structural stability, making it difficult to provide lasting mechanical support to wounds and limiting their individual application. Hydrogels based on synthetic polymers, such as polyacrylamide and polyvinyl alcohol, typically possess excellent mechanical properties and structural controllability, allowing for the preparation of highly resilient hydrogels to meet the mechanical requirements of different wounds. However, these synthetic materials often lack bioactivity, and their biodegradability and the biosafety of their degradation products are also concerns.
[0004] To balance performance and bioactivity, natural and synthetic materials are often combined. However, simple physical blending can lead to weak interfacial bonding between the two phases, hindering effective stress transfer and limiting mechanical reinforcement. Therefore, developing a hydrogel dressing that simultaneously meets mechanical performance requirements and high bioactivity is a key technical challenge. Summary of the Invention
[0005] In view of the above situation and to overcome the defects of the prior art, the purpose of the present invention is to provide a method for preparing collagen wound dressing, so as to at least partially solve the problems mentioned in the background art.
[0006] The technical solution adopted in this invention is as follows: This invention proposes a method for preparing a collagen wound dressing, comprising the following steps: Step S1: Add oxidized astragalus polysaccharide and carboxylated hydrolyzed collagen to water, adjust the pH to 7.0-7.5, and obtain solution A; Step S2: Add carboxymethyl chitosan, acrylamide, N,N'-methylenebisacrylamide, initiator and magnesium salt to water to obtain solution B; Step S3: Mix solution A and solution B, stir evenly, allow to coagulate at room temperature for 3-5 minutes, then heat to 50℃-70℃ for cross-linking reaction for 5-10 hours to obtain the collagen wound dressing.
[0007] In some embodiments of the present invention, in step S1, the concentration of the oxidized astragalus polysaccharide is 3%-6% (w / v); and the concentration of the carboxylated hydrolyzed collagen is 2%-4% (w / v).
[0008] In some embodiments of the present invention, in step S2, the concentration of carboxymethyl chitosan is 1%-3% (w / v); and the concentration of acrylamide is 5%-10% (w / v).
[0009] In some embodiments of the present invention, in step S2, the concentration of N,N'-methylenebisacrylamide is 0.5%-1% (w / v); the concentration of the initiator is 0.1%-0.2% (w / v); and the initiator is ammonium persulfate or potassium persulfate.
[0010] In some embodiments of the present invention, in step S2, the magnesium salt is magnesium chloride, and the concentration of the magnesium chloride is 0.5%-1.5% (w / v).
[0011] In some embodiments of the present invention, in step S3, the volume ratio of the mixture of solution A and solution B is 1:(0.5-1).
[0012] In some embodiments of the present invention, the preparation method of the oxidized astragalus polysaccharide specifically includes the following steps: Astragalus polysaccharide was added to water, sodium periodate was added, and the mixture was stirred and reacted at room temperature in the dark for 8-12 hours. Then, excess ethylene glycol was added to terminate the reaction. After dialysis and freeze-drying, oxidized astragalus polysaccharide was obtained.
[0013] In some embodiments of the present invention, the mass ratio of Astragalus polysaccharide to sodium periodate is 1:(1-1.2).
[0014] In some embodiments of the present invention, the method for preparing the carboxylated hydrolyzed collagen specifically includes the following steps: Hydrolyzed collagen was added to an aqueous solution of glyoxylic acid and reacted at 40℃-50℃ for 4-6 hours to obtain carboxylated hydrolyzed collagen.
[0015] In some embodiments of the present invention, the mass ratio of the hydrolyzed collagen to glyoxylic acid is 1:(0.2-0.4).
[0016] The beneficial effects achieved by this invention are as follows: This invention utilizes the active functionalization design of oxidized astragalus polysaccharide and carboxylated hydrolyzed collagen, combined with the bridging effect of carboxymethyl chitosan, the mechanical enhancement of acrylamide, and the ionic crosslinking of magnesium ions, and employs a two-step molding process to combine the bioactivity of natural materials with the mechanical properties of synthetic polymers at the molecular and network structure levels, thus producing a multifunctional hydrogel dressing with excellent mechanical properties. Attached Figure Description
[0017] Figure 1 This is a flowchart illustrating the preparation method of collagen wound dressing according to an embodiment of the present invention.
[0018] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention and do not constitute a limitation thereof. Detailed Implementation
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to this invention. The preferred embodiments and materials described herein are for illustrative purposes only and do not limit the scope of this application.
[0021] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0022] Reference Figure 1 To address the problems raised in the background art, this invention provides a method for preparing a collagen wound dressing, comprising the following steps: Step S1: Add oxidized astragalus polysaccharide and carboxylated hydrolyzed collagen to water, adjust the pH to 7.0-7.5, and obtain solution A; Step S2: Add carboxymethyl chitosan, acrylamide, N,N'-methylenebisacrylamide, initiator and magnesium salt to water to obtain solution B; Step S3: Mix solution A and solution B, stir evenly, allow to coagulate at room temperature for 3-5 minutes, then heat to 50℃-70℃ for cross-linking reaction for 5-10 hours to obtain collagen wound dressing.
[0023] First, this invention lays the foundation for forming a bioactive initial cross-linked network by constructing a composite prepolymer based on natural active polysaccharides and structured proteins. Oxidized Astragalus polysaccharide, as a key functional component, exhibits a rapid Schiff base reaction between its introduced aldehyde groups and the amino groups of carboxymethyl chitosan in subsequent steps. This is fundamental to achieving room-temperature initial coagulation in step S3, allowing the mixed solution to quickly solidify and facilitating dressing formation and application. Simultaneously, Astragalus polysaccharide itself, as a natural immunomodulator, can actively inhibit excessive inflammation, creating a favorable microenvironment for tissue repair. Synergistically, carboxylated hydrolyzed collagen, as a major component of the extracellular matrix, provides a biomimetic three-dimensional scaffold for cell migration and proliferation, significantly promoting epithelialization and granulation tissue formation. The abundant carboxyl groups on its chain also provide numerous sites for subsequent coordination cross-linking with magnesium ions. This synergistic combination of oxidized Astragalus polysaccharide and carboxylated hydrolyzed collagen ensures that solution A possesses both bioactivity and cross-linkability even before mixing.
[0024] Secondly, solution B designed in this invention constitutes a reinforced liquid phase integrating chemical crosslinking, ionic crosslinking, and physical reinforcement. Carboxymethyl chitosan acts as a bridge connecting solutions A and B; the amino groups on its molecular chain react with the aldehyde groups of oxidized astragalus polysaccharide, which is key to the formation of the Schiff base network. Furthermore, acrylamide and the crosslinking agent N,N'-methylenebisacrylamide can form a covalently crosslinked polyacrylamide network through thermal initiation polymerization in step S3 under the action of an initiator. This polyacrylamide network can serve as the mechanical reinforcing framework of the hydrogel, effectively bearing and dispersing external stress, thereby overcoming the defects of poor mechanical strength and fragility of pure natural hydrogels, resulting in a final dressing with high toughness and high tensile properties. In particular, the introduced magnesium ions can act as an ionic crosslinking agent, coordinating with carboxylated collagen in solution A to form relatively stable ionic bonds. This ionic crosslinking further enhances the network density and mechanical strength of the hydrogel. Moreover, magnesium ions themselves, as an essential trace element for the human body, can promote cell adhesion and metabolism, and exert a synergistic positive effect against inflammation.
[0025] Furthermore, this invention utilizes a two-step crosslinking process—first initial setting at room temperature, then curing by heating—to form a hydrogel with a synergistic dual-network structure of interpenetrating physical and chemical crosslinks. The initial setting at room temperature ensures the material quickly forms its initial structure, facilitating handling. The second step, thermally initiated polymerization, stabilizes and strengthens the entire network structure. This process allows the dressing prepared by this invention to possess excellent mechanical properties while maintaining good flexibility and tissue adhesion, enabling it to adhere closely to the wound surface without easily falling off, and minimizing secondary damage during dressing changes.
[0026] Furthermore, all components used in this invention have good biocompatibility. Astragalus polysaccharide, hydrolyzed collagen, and chitosan are all natural biological macromolecules. This design allows the dressing to have a controllable degradation rate, and its degradation cycle can match the wound healing process, providing protection in the early stages of healing and smoothly degrading and exiting the wound in the later stages.
[0027] In summary, this invention utilizes the active functionalization design of oxidized astragalus polysaccharide and carboxylated hydrolyzed collagen, combined with the bridging effect of carboxymethyl chitosan, the mechanical enhancement of acrylamide, and the ionic crosslinking of magnesium ions, and employs a two-step molding process to combine the bioactivity of natural materials with the mechanical properties of synthetic polymers at the molecular and network structure levels, thereby producing a multifunctional hydrogel dressing with excellent mechanical properties.
[0028] In some embodiments, in step S1, the concentration of oxidized astragalus polysaccharide is 3%-6% (w / v); the concentration of carboxylated hydrolyzed collagen is 2%-4% (w / v). Setting the concentration of oxidized astragalus polysaccharide within an appropriate range facilitates the full cross-linking of oxidized astragalus polysaccharide with carboxymethyl chitosan, while also fully leveraging its immunomodulatory function. Setting the concentration of carboxylated hydrolyzed collagen within an appropriate range facilitates its full coordination with magnesium ions, enhancing the mechanical strength of the hydrogel, while also fully leveraging its biological activity.
[0029] In some embodiments, in step S2, the concentration of carboxymethyl chitosan is 1%-3% (w / v); the concentration of acrylamide is 5%-10% (w / v). Setting the concentration of carboxymethyl chitosan within a suitable range facilitates the full cross-linking of carboxymethyl chitosan and oxidized astragalus polysaccharide, while fully leveraging their inherent antibacterial and healing-promoting effects. Setting the concentration of acrylamide within a suitable range allows for the improvement of the dressing's mechanical properties through a moderate polymerization and cross-linking density.
[0030] In some embodiments, in step S2, the concentration of N,N'-methylenebisacrylamide is 0.5%-1% (w / v); the concentration of the initiator is 0.1%-0.2% (w / v). By setting the concentration of N,N'-methylenebisacrylamide within a suitable range, appropriate crosslinking points can be formed, ensuring the mechanical properties of the crosslinked network; by setting the concentration of the initiator within a suitable range, the covalent crosslinking of acrylamide and N,N'-methylenebisacrylamide can be fully carried out, generating a relatively stable covalent crosslinked network. The initiator can be ammonium persulfate or potassium persulfate.
[0031] In some embodiments, in step S2, the magnesium salt is magnesium chloride, and the concentration of magnesium chloride is 0.5%-1.5% (w / v). By setting the concentration of magnesium chloride within a suitable range, it can form appropriate coordination bonds with the carboxyl groups on the carboxylated hydrolyzed collagen and carboxymethyl chitosan chains, effectively enhancing the compactness and mechanical strength of the hydrogel network and improving its resistance to compression and deformation.
[0032] In some embodiments, in step S3, the volume ratio of solution A to solution B is 1:(0.5-1). By setting the volume ratio of solution A to solution B within a suitable range, a more stable cross-linked network can be formed. At the same time, the bioactivity of natural materials and the mechanical properties of synthetic polymers are balanced, thereby obtaining a hydrogel dressing with excellent mechanical properties and preserved bioactive components.
[0033] In some embodiments, the preparation method of oxidized astragalus polysaccharide specifically includes the following steps: adding astragalus polysaccharide to water, adding sodium periodate, stirring and reacting at room temperature in the dark for 8-12 hours, then adding excess ethylene glycol to terminate the reaction, and obtaining oxidized astragalus polysaccharide after dialysis and freeze-drying. The oxidation reaction with sodium periodate can achieve the conversion of hydroxyl groups to aldehyde groups on the astragalus polysaccharide molecular chain. At the same time, the reaction conditions are relatively mild, effectively avoiding excessive oxidative degradation of astragalus polysaccharide.
[0034] In some embodiments, the mass ratio of Astragalus polysaccharide to sodium periodate is 1:(1-1.2). By setting the molar ratio of Astragalus polysaccharide to sodium periodate within a suitable range, the aldehyde alkylation of Astragalus polysaccharide can be fully achieved while preventing excessive oxidation. This allows for the introduction of sufficient cross-linking sites while maximizing the integrity of the Astragalus polysaccharide molecular backbone and its inherent biological activity.
[0035] In some embodiments, the preparation method of carboxylated hydrolyzed collagen specifically includes the following steps: adding hydrolyzed collagen to an aqueous solution of glyoxylic acid, reacting at 40℃-50℃ for 4-6 hours to obtain carboxylated hydrolyzed collagen. Glyoxylic acid introduces carboxyl groups onto the hydrolyzed collagen, providing sufficient coordination sites for subsequent construction of an ionic cross-linking network with magnesium ions. The hydrolyzed collagen can be obtained through enzymatic hydrolysis, for example, by adding animal-derived collagen (such as pigskin or bovine hide) to deionized water, adjusting the pH to 6.0-8.0, controlling the temperature at 45℃-60℃, adding 1-3% (by weight) of protease, and stirring the reaction for 4-6 hours.
[0036] In some embodiments, the mass ratio of hydrolyzed collagen to glyoxylic acid is 1:(0.2-0.4). By setting the mass ratio of hydrolyzed collagen to glyoxylic acid within a suitable range, the hydrolyzed collagen can have adequate carboxyl groups, thereby forming an effective ionic cross-linking network with magnesium ions, while retaining the natural cell adhesion effect of the hydrolyzed collagen molecular chain.
[0037] The present invention will be further described below by way of specific embodiments.
[0038] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods already existing in the art; unless otherwise specified, the experimental materials used in the following embodiments are all purchased from commercial channels.
[0039] Example 1: Astragalus polysaccharide was added to water, and sodium periodate was added. The mass ratio of astragalus polysaccharide to sodium periodate was 1:1. The mixture was stirred at room temperature in the dark for 8 hours. Then, excess ethylene glycol was added to terminate the reaction. After dialysis and freeze-drying, oxidized astragalus polysaccharide was obtained.
[0040] Hydrolyzed collagen was added to an aqueous solution of glyoxylic acid at a mass ratio of 1:0.2. The mixture was reacted at 40°C for 4 hours to obtain carboxylated hydrolyzed collagen.
[0041] Oxidized Astragalus polysaccharide and carboxylated hydrolyzed collagen were added to water to prepare a mixed solution with an oxidized Astragalus polysaccharide concentration of 3% (w / v) and a carboxylated hydrolyzed collagen concentration of 2% (w / v). The pH was adjusted to 7.0 to obtain solution A. Carboxymethyl chitosan, acrylamide, N,N'-methylenebisacrylamide, ammonium persulfate initiator, and magnesium chloride were added to water to prepare solution B, which contained 1% (w / v) carboxymethyl chitosan, 5% (w / v) acrylamide, 0.5% (w / v) N,N'-methylenebisacrylamide, 0.1% (w / v) initiator, and 0.5% (w / v) magnesium chloride. Solution A and solution B were mixed at a volume ratio of 1:0.5 and stirred at 300 rpm for 2 minutes using a mechanical stirrer. The mixture was then allowed to coagulate at room temperature for 3 minutes. After that, it was placed in an oven and heated to 50°C for a cross-linking reaction for 10 hours to obtain collagen wound dressing.
[0042] Example 2: Astragalus polysaccharide was added to water, and sodium periodate was added. The mass ratio of astragalus polysaccharide to sodium periodate was 1:1.2. The mixture was stirred at room temperature in the dark for 12 hours. Then, excess ethylene glycol was added to terminate the reaction. After dialysis and freeze-drying, oxidized astragalus polysaccharide was obtained.
[0043] Hydrolyzed collagen was added to an aqueous solution of glyoxylic acid at a mass ratio of 1:0.4. The mixture was reacted at 50°C for 6 hours to obtain carboxylated hydrolyzed collagen.
[0044] Oxidized Astragalus polysaccharide and carboxylated hydrolyzed collagen were added to water to prepare a mixed solution with an oxidized Astragalus polysaccharide concentration of 6% (w / v) and a carboxylated hydrolyzed collagen concentration of 4% (w / v). The pH was adjusted to 7.5 to obtain solution A. Carboxymethyl chitosan, acrylamide, N,N'-methylenebisacrylamide, ammonium persulfate initiator, and magnesium chloride were added to water to prepare solution B, which contained 3% (w / v) carboxymethyl chitosan, 10% (w / v) acrylamide, 1% (w / v) N,N'-methylenebisacrylamide, 0.2% (w / v) initiator, and 1.5% (w / v) magnesium chloride. Solution A and solution B were mixed at a volume ratio of 1:1 and stirred at 300 rpm for 2 minutes using a mechanical stirrer. The mixture was then allowed to coagulate at room temperature for 5 minutes. After that, it was placed in an oven and heated to 70°C for a cross-linking reaction for 5 hours to obtain collagen wound dressing.
[0045] Example 3: Consistent with Example 1, except that solution A and solution B are mixed in a volume ratio of 1:0.6.
[0046] Example 4: Consistent with Example 1, except that solution A and solution B are mixed in a volume ratio of 1:0.7.
[0047] Example 5: Consistent with Example 1, except that solution A and solution B are mixed at a volume ratio of 1:0.8.
[0048] Example 6: Consistent with Example 1, except that solution A and solution B are mixed at a volume ratio of 1:0.9.
[0049] Comparative Example 1: Consistent with Example 1, except that acrylamide, N,N'-methylenebisacrylamide and the initiator ammonium persulfate are not added to solution B.
[0050] Comparative Example 2: Consistent with Example 1, except that hydrolyzed collagen is used instead of carboxylated hydrolyzed collagen in solution A, and magnesium chloride is not added to solution B.
[0051] Test method: Mechanical properties: The tensile strength and elongation at break of the hydrogel were tested using an electronic universal testing machine (WDW02) at 25°C with a weight sensor of 200 N. The selected crosshead speed was 20 mm / min. The hydrogel was prepared into strips, and its thickness was measured to be 10 mm using vernier calipers. The test results are shown in Table 1.
[0052] Swelling properties: The hydrogel was freeze-dried, and its initial weight (W0) was recorded. It was then immersed in a beaker containing phosphate buffer solution at room temperature. After 72 hours, the sample was removed, the surface moisture was blotted dry with filter paper, and the sample was weighed. Weight is expressed in W. s The swelling ratio is calculated using the following formula: Swelling ratio = [(W s -W0) / W0]×100%. The test results are shown in Table 1.
[0053] Table 1
[0054] Referring to the test results in Table 1, all examples exhibited good tensile strength and elongation at break, demonstrating that mechanically robust dual-network hydrogels can be successfully constructed within the parameter range set in this invention. Comparative Example 1, lacking acrylamide monomer, crosslinking agent, and initiator, exhibited lower tensile strength and elongation at break. Comparative Example 2 also showed lower tensile strength and elongation at break compared to Example 1, indicating that carboxylated hydrolyzed collagen and magnesium ions constitute an ionic crosslinking network, which can improve the mechanical properties of the hydrogel.
[0055] The swelling ratios of Examples 1-6 were around 500%, providing good swelling performance and avoiding excessive water absorption. This ensured that the dressing maintained its shape on the wound surface and did not compress the wound due to excessive swelling. The swelling ratio of Comparative Example 1 was meaningless due to complete disintegration. Comparative Example 2 exhibited an extremely high swelling ratio due to the lack of a dense magnesium ion cross-linking network. This excessive swelling could lead to the dressing easily ulcerating and losing its effective protection of the wound surface.
[0056] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0057] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a collagen wound dressing, characterized in that, Includes the following steps: Step S1: Add oxidized astragalus polysaccharide and carboxylated hydrolyzed collagen to water, adjust the pH to 7.0-7.5, and obtain solution A; Step S2: Add carboxymethyl chitosan, acrylamide, N,N'-methylenebisacrylamide, initiator and magnesium salt to water to obtain solution B; Step S3: Mix solution A and solution B, stir evenly, allow to coagulate at room temperature for 3-5 minutes, then heat to 50℃-70℃ for cross-linking reaction for 5-10 hours to obtain the collagen wound dressing. The method for preparing the carboxylated hydrolyzed collagen specifically includes the following steps: adding hydrolyzed collagen to an aqueous solution of glyoxylic acid, reacting at 40℃-50℃ for 4-6 hours to obtain carboxylated hydrolyzed collagen; the mass ratio of hydrolyzed collagen to glyoxylic acid is 1:(0.2-0.4).
2. The preparation method according to claim 1, characterized in that, In step S1, the mass-volume concentration of the oxidized astragalus polysaccharide in solution A is 3%-6%; the mass-volume concentration of the carboxylated hydrolyzed collagen in solution A is 2%-4%.
3. The preparation method according to claim 1, characterized in that, In step S2, the mass-volume concentration of carboxymethyl chitosan in solution B is 1%-3%; the mass-volume concentration of acrylamide in solution B is 5%-10%.
4. The preparation method according to claim 1, characterized in that, In step S2, the N,N'-methylenebisacrylamide has a mass-volume concentration of 0.5%-1% in solution B; the initiator has a mass-volume concentration of 0.1%-0.2% in solution B; and the initiator is ammonium persulfate or potassium persulfate.
5. The preparation method according to claim 1, characterized in that, In step S2, the magnesium salt is magnesium chloride, and the mass-volume concentration of magnesium chloride in solution B is 0.5%-1.5%.
6. The preparation method according to claim 1, characterized in that, In step S3, the volume ratio of solution A to solution B is 1:(0.5-1).
7. The preparation method according to claim 1, characterized in that, The preparation method of the oxidized astragalus polysaccharide specifically includes the following steps: Astragalus polysaccharide was added to water, sodium periodate was added, and the mixture was stirred and reacted at room temperature in the dark for 8-12 hours. Then, excess ethylene glycol was added to terminate the reaction. After dialysis and freeze-drying, oxidized astragalus polysaccharide was obtained.
8. The preparation method according to claim 7, characterized in that, The mass ratio of Astragalus polysaccharide to sodium periodate is 1:(1-1.2).
Citation Information
Patent Citations
Preparation method of high tenacity double-network physical crosslinking self-repairing hydrogel
CN109054052A
Hemostatic material capable of rapidly stopping bleeding and preparation method thereof
CN114887110A